Poverty, inequality, and spillover in Mexico's education, health, and nutrition program - Handa, Sudhanshu; Huerta, Mari-Carmen; Perez, Raul; Straffon, Beatriz (International Food Policy Research Institute, 2001)
This report provides an evaluation of the community-level effects of the Programa Nacional de Educacion, Salud, y Alimentacion (PROGRESA) using household-level data from various rounds of PROGRESA’s evaluation sample (the Encuesta de Evaluacion de los Hogares [ENCEL] surveys).Other reports in the evaluation series have focused on the direct effects of PROGRESA, using the control and treatment groups in the ENCELS. The objective of this report is slightly different, in that it explores the possible spillover effects of the program on the wider community. Hence, instead of focusing on program effects at the individual level, the study focuses on aggregate community-level indicators of well being such as poverty, inequality, and school and health care attendance rates, in order to assess the impact of PROGRESA at this level. Using the data sets mentioned above, the authors developed five indicators with which to measure the potential impact of PROGRESA at the community level: (1) changes in rates of relative poverty; (2) changes in inequality; (3) school continuation rates; (4) changes in nutrition surveillance rates; and (5) changes in prices (inflation).